GLUCOCORTICOIDS ENHANCE IN VIVO EXPOSURE‐BASED THERAPY OF SPIDER PHOBIA. Issue 5 (21st November 2013) - Soravia, Leila M.; Heinrichs, Markus; Winzeler, Livia; Fisler, Melanie; Schmitt, Wolfgang; Horn, Helge; Dierks, Thomas; Strik, Werner; Hofmann, Stefan G.; de, Dominique J.‐F.
<x xml:space="preserve">Abstract</x> Background Preclinical and clinical studies indicate that the administration of glucocorticoids may promote fear extinction processes. In particular, it has been shown that glucocorticoids enhance virtual reality based exposure therapy of fear of heights. Here, we investigate whether glucocorticoids enhance the outcome of in vivo exposure‐based group therapy of spider phobia. Methods In a double blind, block‐randomized, placebo‐controlled, between‐subject study design, 22 patients with specific phobia of spiders were treated with two sessions of in vivo exposure‐based group therapy. Cortisol (20 mg) or placebo was orally administered 1 hr before each therapy session. Patients returned for a follow‐up assessment one month after therapy. Results Exposure‐based group therapy led to a significant decrease in phobic symptoms as assessed with the Fear of Spiders Questionnaire (FSQ) from pretreatment to immediate posttreatment and to follow‐up. The administration of cortisol to exposure therapy resulted in increased salivary cortisol concentrations and a significantly greater reduction in fear of spiders (FSQ) as compared to placebo at follow‐up, but not immediately posttreatment. Furthermore, cortisol‐treated patients reported significantly less anxiety during standardized exposure to living spiders at follow‐up than placebo‐treated subjects. Notably, groups did not differ in phobia‐unrelated state‐anxiety before and after the exposure sessions and at follow‐up. Conclusions These findings indicate that adding cortisol to in vivo exposure‐based group therapy of spider phobia enhances treatment outcome.